Silence, ye women! God is at work in the womb. Psalm 139 as illustration of Israel's embodied patriarchal theology of containment - Coetzee, Johan H. (Old Testament Essays, 2005)
For Israel the socially constructed ideal body was symbolized as the whole and pure body, especially the male body. The event of birth was ritually impure not only because blood was involved but also because of the breaking of boundaries when a female body broke open in order to give birth to another body. Pregnancy did not only belong to the woman herself. It was a state of the developing foetus, for which the woman was a container that needed to be socially contained and controlled. In Psalm 139 a glimpse into the womb is given. Yahweh is depicted as skilfully dedicating himself to the creation of a male body deep inside this exclusive workplace of his. The pregnant woman is silenced by the glorification of the male embryo / baby and his male creator. This paper looks into the way Psalm 139 reflects on the body-politics of silencing the women in Israel's theology.
free